(untitled) (Bangladesh Journal of Medical Science, 2020)
World Health Organization recommends doctor population ratio as 1: 1000 and in India the ratio is 0.62: 1000. With the ever growing population and tremendous patient pool in India the significant challenge faced by clinicians is lack of skilled allied health professionals who can assist in providing timely, unbiased, critically appraised health information. Pharmacists are the most accessible health professionals and thereby crucial in facilitating rational medication usage and working closely with the public and multidisciplinary health care team. The goal of patient care can be achieved through the focused skill development programs embedded in health students’ curriculum. Indian pharmacy curriculum should be fostered with inclusion of evidence based medicine focused training programs, workshops, case studies, digital stories, e - pocket cards and simulations. This article represents current status of evidence based medicine learning and teaching in Indian pharmacy curriculum. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.603-608